GLOBULAR CLUSTERS AS GRAVITATIONAL LENSES. OBSERVATIONAL TEST - Yushchenko, A. V. (Одеські астрономічні публікації, 2017)
Let us suppose that globular clusters in the halos of distant galaxies can act as a gravitational lenses. The observational test for this hypothesis is the overdensity of star-like images near foreground galaxies. We analyzed USNO A2.0 catalog in the vicinity of 35862 galaxies with redshifts 0.01-0.33 and found that mean overdensity of objects brighter than 21m is near 100 objects per galaxy.